2013
DOI: 10.1016/j.foodres.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aroma compounds in Portuguese extra virgin olive oils from Galega Vulgar and Cobrançosa cultivars using GC–O and GC×GC–ToFMS

Abstract: Aroma compounds of virgin olive oils extracted from two olive cultivars-Galega Vulgar and Cobrançosagrown in Beira Baixa region in central Portugal were investigated. Gas chromatography-olfactometry (GC-O) was carried out to select the important odorants for subsequent comprehensive gas chromatography/time of flight mass spectrometry (GC × GC-ToFMS) analysis. By GC-O fifteen odorants were identified. For the quantification of volatile compounds, headspace solid phase microextraction (SPME) technique was optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 42 publications
6
44
0
1
Order By: Relevance
“…All the volatile compounds determined in this study were previously identified as important VOO aroma compounds and investigated for their sensory significance and their odour thresholds were determined (Kesen, Kelebek, Sen, Ulas, & Selli, 2013;Luna et al, 2006;Morales, Rios, & Aparicio, 1997;Peres et al, 2013). As reported by the cited authors, some volatile compounds identified in our samples were found to contribute to the green odour notes characteristic of aroma of high quality VOO, whereas other compounds were reported as responsible of unpleasant aroma odours.…”
Section: Analysis Of Volatile Compoundssupporting
confidence: 60%
“…All the volatile compounds determined in this study were previously identified as important VOO aroma compounds and investigated for their sensory significance and their odour thresholds were determined (Kesen, Kelebek, Sen, Ulas, & Selli, 2013;Luna et al, 2006;Morales, Rios, & Aparicio, 1997;Peres et al, 2013). As reported by the cited authors, some volatile compounds identified in our samples were found to contribute to the green odour notes characteristic of aroma of high quality VOO, whereas other compounds were reported as responsible of unpleasant aroma odours.…”
Section: Analysis Of Volatile Compoundssupporting
confidence: 60%
“…This choice is in good agreement with the previous studies carried out in GC × GC to characterize the HS of other kinds of edible oils [32,34,37].…”
Section: Evaluation Of the Impact Of The Column Set On The Separationsupporting
confidence: 90%
“…Indeed, SPME has the advantages to provide a rapid sampling at low cost and can easily be automated [31]. The combination of HS-SPME and GC × GC, therefore, provides a powerful tool for concentration and efficient separation of the compounds present in the HS of edible oils [32].…”
Section: Introductionmentioning
confidence: 99%
“…[19] The most prevalent C6 aldehyde present among five olive varieties was (E)-2-hexenal, with concentrations ranging from 10.74 to 26.51 mg/L (Table 2), this result is in accordance with the literature data obtained from other monovarietal olive oils. In fact, (E)-2-hexenal is the most abundant volatile compound in European, [23][24][25][26][27][28][29] Tunisian, [20,30] and Moroccan [21] olive oils. Surprisingly, EVOO obtained from the variety Ferkani did not contain (E)-2-hexenal (Table 2), whereas the latter was found at relatively low amounts in Aaleh and Abani varieties (2.26 and 0.38 mg/L, respectively).…”
Section: Effect Of Cultivar On the Volatile Compounds In Algerian Evoomentioning
confidence: 99%